The effect of body build and BMI on aerobic test performance in school children (10-15 years) - Slinger, J. D.; Verstappen, F. T.; van Breda, E.; Kuipers, H. (Journal of Sports Science & Medicine, 2006)
Body Mass Index (BMI) has often questionably been used to define body build. In the present study body build was defined more specifically using fat free mass index (FFMI = fat free mass normalised to the stature) and fat mass index (FMI = fat mass normalised to stature). The body build of an individual is 'solid' in individuals with a high FFMI for their FMI and is 'slender' in individuals with a low FFMI relative to their FMI. The aim of the present study was to investigate the association between aerobic test performance and body build defined as solid, average or slender in 10 to 15 year old children. Five-hundred-and-two children (53% boys) aged 10 to 15 years of age were included in the study. Aerobic test performance was estimated with an incremental cycle ergometer protocol and a shuttle run test. BMI and percentage fat (by skin folds) were determined to calculate FMI and FFMI. After adjustment for differences in age, gender and body mass the solid group achieved a significantly higher maximal power output (W) and power output relative to body mass (W/kg) during the cycle test (p < 0.05) and a higher shuttle-run score (p < 0.05) compared to the slender group. The power output relative to FFM (W/kg FFM) was comparable (p > 0.05) between different body build groups. This study showed that body build is an important determinant of the aerobic test performance. In contrast, there were no differences in aerobic test performance per kilogramme FFM over the body build groups. This suggests that the body build may be determined by genetic predisposition.